TOURISM ON INSTAGRAM: A SOCIAL NETWORK ANALYSIS - Tahalea, Sylvert Prian; Salouw, Elvis; Wibowo, Astrid Wahyu Adventri (PATTIMURA UNIVERSITY, 2022)
This research aims to analyze and describe the development of tourism in Maluku Province, Indonesia on Instagram. The data used in this study are hashtags from several excellent tourist attractions or tourist priorities set by the maluku province tourism office. The data is then processed using social network analysis to find the level of importance and connectedness of tourism hashtags with other hashtags used in image captions on Instagram posts. The results showed that there are nine hashtags that have an important role in the network because they have high values in the measurement of degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality. The hashtags are #maluku, #ambon, #natsepa, #pulauosi, #pulaubair, #beach, #repost, #indonesia, and #namalatu. Two of nine hashtags have a high betweenness centrality value, namely #natsepa that represent natsepa beach tourism and #namalatu that represents namalatu beach tourism. Both of these tours have a high value betweenness centrality with a different form of hashtags, namely #natsepa.id and #namalatu02. This research conducted using social network analysis degree measurements such as degree, betweeness, closeness, and eigenvector to analyze insight of tourism topics in Instagram. The result of this research can give insights to the tourism actors, especially in Maluku Province, of how the hashtags are connected and related. The relation of the hashtags can be used as social media marketing strategy.